Pediatric Upper Extremity Replantation: Courage in the Face of a Life-altering Injury. Issue 7 (July 2018) - Sivak, Wesley N.; Schusterman, M. Asher; Grunwaldt, Lorelei J.
Abstract : Background: Pediatric plastic surgeons perform reconstructive surgeries for various congenital, oncologic, and traumatic injuries. Methods: Our Children's Hospital of Pittsburgh of University of Pittsburgh Medical Center (UPMC) Plastic Surgery team was tasked to care for a young man who suffered a proximal humeral amputation of his dominant upper extremity. Results: A multidisciplinary team collaborated throughout his entire acute care and postoperative course, guiding treatment and care in effort to maximize function of his replanted extremity. Conclusions: This case report details the patient's unique journey and highlights his determination and courage to return back to a normal life. Abstract : Supplemental Digital Content is available in the text.